Determination of the technical state of buildings and constructions after force and temperature influences - Gordiuk, Mykola; Semynoh, Mykola; Holodnov, Oleksandr; Tkachuk, Igor (Technology audit and production reserves, 2019)
The object of research is the technical condition and bearing capacity of reinforced concrete structures of buildings and structures after power and high-temperature influences. Calculation methods, which are recommended by the current regulatory documents of Ukraine, do not always allow to correctly predict the growth of structural deformations and assess the real stock of bearing capacity. One of the most problematic places is the calculation of structures working under forced displacements of supports and/or possible high-temperature influences. The situation is further aggravated by the fact that calculations are carried out, as a rule, using non-deformable schemes. Strengthening of structures of buildings that have suffered damage after various impacts is usually carried out using metal elements. At the same time, the main thing remains to perform structural analysis for the justified purpose of the sections of reinforcing elements. In the course of the study, various methods were used, primarily modeling the operation of structures using the finite element method and modern computer systems. This is due to the fact that the proposed method for solving the problem has a number of features, in particular, it allows determining the distribution of forces in the building elements after changing the stiffness characteristics or introducing additional core elements into the design scheme. In the course of solving the problem, the appearance and development of cracks is modeled by changing the stiffness characteristics of the elements. The efforts that could have arisen in the elements of the building and reinforcement are obtained. Thanks to this, it is possible to make decisions about the possibility of further operation, reinforcement or replacement of structures. Changing the conditions of consolidation is considered as action on the part of the foundation. Compared with similar well-known calculation methods, this approach makes it possible to predict changes in the technical condition over time, that is, taking into account changes in fixing conditions and characteristics of building materials will allow a more reasonable approach to assessing the stress-strain state and the residual life of the structure or structure as a whole.